2019
DOI: 10.1002/ejp.1487
|View full text |Cite
|
Sign up to set email alerts
|

The role of the spinal cyclooxygenase (COX) for incisional pain in rats at different developmental stages

Abstract: Background Cyclooxygenase enzymes (COX)‐1 and COX‐2 are important targets for pain relief after surgery, but the spinal contribution of both isoforms is still unclear, e.g., from a developmental point of view. Here, we studied changes of spinal COX‐1 and COX‐2 expression and their functional relevance in rats of different ages for pain‐related behaviour after incision. Methods Mechanical paw withdrawal thresholds (PWT) were assessed before and after incision and after intrathecal administration (IT) of SC‐560 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…For example, in previous neuropathic pain studies, many other examples for time-specific changes in signaling have been reported (Cobos et al, 2018;Segelcke et al, 2021a). In an earlier study, we identified a developmental variation in the function of cyclooxygenase 2 in postoperative pain (Segelcke et al, 2020), further reinforcing the link of function in development of pain disease. Here, for example, we described increased GAT-1 expression during the early phase 4 h following incision (initiation phase), but not at later time points (POD1, POD3 and POD5) during the maintenance phase, which would have been missed if only later time points had been investigated.…”
Section: Discussionsupporting
confidence: 62%
“…For example, in previous neuropathic pain studies, many other examples for time-specific changes in signaling have been reported (Cobos et al, 2018;Segelcke et al, 2021a). In an earlier study, we identified a developmental variation in the function of cyclooxygenase 2 in postoperative pain (Segelcke et al, 2020), further reinforcing the link of function in development of pain disease. Here, for example, we described increased GAT-1 expression during the early phase 4 h following incision (initiation phase), but not at later time points (POD1, POD3 and POD5) during the maintenance phase, which would have been missed if only later time points had been investigated.…”
Section: Discussionsupporting
confidence: 62%
“…The differences in the effect of ropivacaine between the studies may be due to the different method of drug administration [16,[37][38][39][40]. However, strain differences (domestic pigs vs. minipigs) [41], sex [42], and age [43,44] may also affect the action of ropivacaine.…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral nerve injury induced by axotomy and TG extraction during our experiments do not rule out the transcriptional alterations of neuroregeneration and neuroprotection genes in neuron. Moreover, the hub genes, such as Actb , Gsk3b , and mt-Co1 , were identified, which are closely correlated with pain development ( Liu et al, 2017 ; Noori et al, 2020 ; Segelcke et al, 2020 ). And the roles and mechanisms of several potential novel targets in orofacial inflammatory pain, such as Scn7a and Zbtb20 in PEP1, Rgs7bp in PEP2, and Bhlha9 in cLTMR, require further exploration.…”
Section: Discussionmentioning
confidence: 99%